Towards “The Nature and Secrets of Music”: W. C. Printz and the natural history tradition - Wessel, Jan Andreas (Interdisciplinary Studies in Musicology, 2021)
The present article provides arecontextualization of Wolfgang Caspar Printz’s (1641–1717) landmark music history published in 1690 (Historische Beschreibung der edelen Sing- und Kling-Kunst). later commentators have read it as a primitive, naïve and even failed attempt at writing the history of music. Still, they seem to agree that the text, in virtue of its subject matter, forms part of a canon of music historiography. The present article will seek the interpretative key in the wider intellectual context, outside of the narrow confines of texts about the musical past. It will advance the thesis that Printz built his music historiography from elements of the natural history tradition. Two arguments support this thesis. First, it will be argued that the organization of the material in chapters XIv, Xv and XvI betrays the influence of a classical version of taxonomy closely associated with the natural history tradition. Secondly, that Printz’s inquiry into the purpose of music reveals his reliance on a concept of nature similarly rooted in natural history.